The Influence Of Customer Experience Towards Flip’s Customer Satisfaction - Yahya, Muhammad Auliya; Saraswati, Trisha Gilang (eProceedings of Management, 2023)
Along with the development in this era of globalization, the internet has influenced all of aspects such as people lifestyle, business, andcompany. Many companies also use information technology and the Internet to develop various types of services, especially in thefield of financial technology. Flip is an application that owned by PT Fliptech Lentera Inspirasi Pertiwi which aims to help people sendmoney securely without any transaction fee. However, many factors that can affect the can review their satisfaction. By seeing theimportance of this study to understand the factors of customer experience that can influence customer satisfaction of Flip’s users inIndonesia. This research uses quantitative descriptive and causal based on the customer experience and customersatisfaction. The sample in this research amounted to 100 respondents who have been use Flip’s service. Then, thesampling technique used is probability sampling. The regression results found that customer experience has significanteffect on customer satisfaction, because the sig. value obtained is 0.000 or < 0.05. Likewise, customer intern ofcustomer such as the company could give offering free admin fee.